Vaccinating in Different Settings: Best Practices from Italian Regions - Carlo Signorelli; Flavia Pennisi; Anna Carole D’Amelio; Michele Conversano; Sandro Cinquetti; Lorenzo Blandi; Giovanni Rezza (Vaccines)
Background: The success of vaccination programs depends on a complex interplay of logistical, social, and structural factors. The objective of this study was to analyze the different approaches to vaccine administration implemented by several Italian regions since the onset of the SARS-CoV-2 pandemic. Methods: After careful qualitative review of information gathered from scientific articles, official reports (grey literature), contact with regional health authorities, and local health departments, five vaccination strategies across several Italian regions focusing on alternative vaccine providers and/or settings were identified. The innovative practices implemented by different actors covered specific topics and were then examined and described in detail. Results: In Veneto, where prevention departments were the main actor, herpes zoster vaccination coverage for the 65-year-old cohort increased from 44.4% to 54.9%; in Tuscany, family pediatricians administered 64% of all childhood vaccines; in Liguria, pharmacies delivered 70.1% of COVID-19 vaccines, while vaccinating in schools in Taranto led to higher human papilloma virus vaccination rates compared to regional and national averages. Finally, in all the regions, hospitals focused on vaccinating healthcare workers and vulnerable populations. Conclusions: The positive outcomes of these five experiences may, in a context of limited resources, encourage other national and international entities to adopt innovative practices, which offer new perspectives beyond the traditional delivery methods (i.e., local health authority vaccination centers for childhood and adolescent immunizations, and family doctors for adults and the elderly). These strategies suggest the efficacy of specific local approaches favored by regional autonomy in optimizing vaccine distribution and coverage.